Are platelets more than a model of brain neurons? - Ilaria Canobbio; Silvia Stella Barbieri (Bleeding, Thrombosis and Vascular Biology, 2022)
For many years, the brain was considered as a closed system protected by the blood-brain barrier (BBB), where only the hormones produced by the body can mediate the interplay between the brain and the blood. Indeed, hormones, crossing the BBB and binding to specific receptors on the brain cells, regulates neuronal and synaptic plasticity and neurogenesis [...].